Dompet Dhuafa Waspada Strategy in Empowering the Mustahik Economy for Sustainable Economic Development - Berutu, Irsyadiah Dermaini; Marliyah, Marliyah; Harahap, Rahmat Daim (Tasharruf: Journal Economics and Business of Islam, 2025)
Productive zakat is a strategic instrument for reducing poverty and enhancing community welfare, yet its implementation often encounters managerial and contextual challenges. This study aims to analyze the strategy of Dompet Dhuafa Waspada in Medan’s in empowering mustahik through productive zakat programs, specifically those involving business capital grants, skills training, and continuous mentoring within the Menjahit Harapan Dhuafa programme, Livestock Center, and Rumah Tempe initiatives. Using a qualitative case study approach supported by the SOAR (Strengths, Opportunities, Aspirations, Results) framework, data were obtained through in-depth interviews, observations, questionnaires, and documentation. The findings show that Dompet Dhuafa Waspada in Medan possesses strong internal capacities (score 19.6) and clear strategic aspirations (score 19.4), positioning the institution in the SA quadrant, which emphasizes maximizing strengths to achieve long-term goals. The study reveals that the implementation of productive zakat includes structured business assistance, capital distribution, skills development, and marketplace facilitation; however, the program also faces several challenges. These include limited capital scalability, variability in mustahik entrepreneurial readiness, dependence on external market dynamics, and constraints in long-term monitoring. Despite these obstacles, the program successfully increases mustahik income, improves business independence, and generates measurable socio-economic benefits when integrated with consistent mentoring and cross-sector collaboration. This research provides a balanced evaluation of both the achievements and limitations of productive zakat implementation in Medan and offers an empirical foundation for strengthening institutional strategies and public policies that support sustainable poverty alleviation aligned with the Sustainable Development Goals.